Pobot z odstopljeno terjatvijo - Dugar, Gregor (Pravni letopis, 2012)
A creditor may assign his claim by a contract entered into with a third party. A debtor shall not be affected in his rights by a cession. A debtor may raise against an assignee, in addition to objections he has against him, also those which he was able to raise against the assignor until the moment of being notified of the assignment. The article deals with the debtor's right to set-off with an assigned claim.
Keywords: cesija; terjatve; upniki